A Question of Coherence: The Proposals on EU Contract Rules on Digital Content and Online Sales. Issue 5 (October 2016) - Lehmann, Matthias
Digitalization is revolutionizing our life. In response to its ever growing impact, the European Commission has tabled two proposals for new directives, one pertaining to contracts for the supply of digital content, the other regarding online and other distance sales of goods. This contribution analyses both proposals critically. It questions the need for having a separate regime encompassing contracts for sale of digital content in light of the possibility of adapting the existing legal framework to reflect the particularities of such agreements. It also warns against adopting more specific rules on online sales, which would further widen the gap in their treatment when compared to face-to-face agreements. The author bemoans the confusion and contradictions the new proposals would introduce to EU consumer law. The choice of a maximum harmonization approach extends this lack of coherence into Member State law. Even worse, the EU legislator interferes with areas that have so far been the exclusive domain of national civil law, such as determining adequate levels of damages or the consequences of termination. Despite the need for compromise, the author suggests that the Commission should not seek them at any cost, but stick to principles of good law-making in multi-level governance systems.